Effect of automated versus manual emergency braking on rear seat adult and pediatric occupant precrash motion. (12th June 2019) - Graci, Valentina; Douglas, Ethan; Seacrist, Thomas; Kerrigan, Jason; Mansfield, Julie; Bolte, John; Sherony, Rini; Hallman, Jason; Arbogast, Kristy B.
Abstract: Objective: Emergency braking can potentially generate precrash occupant motion that may influence the effectiveness of restraints in the subsequent crash, particularly for rear-seated occupants who may be less aware of the impending crash. With the advent of automated emergency braking (AEB), the mechanism by which braking is achieved is changing, potentially altering precrash occupant motion. Further, due to anatomical and biomechanical differences across ages, kinematic differences between AEB and manual emergency braking (MEB) may vary between child and adult occupants. Therefore, the objective of this study was to quantify differences in rear-seated adult and pediatric kinematics and muscle activity during AEB and MEB scenarios. Methods: Vehicle maneuvers were performed in a recent model year sedan traveling at 50 km/h. MEB (acceleration ∼1 g ) was achieved by the driver pressing the brake pedal with maximum effort. AEB (acceleration ∼0.8 g ) was triggered by the vehicle system. Inertial and Global Positioning System data were collected. Seventeen male participants aged 10–33 were restrained in the rear right passenger seat and experienced each maneuver twice. The subjects' kinematics were recorded with an 8-camera 3D motion capture system. Electromyography (EMG) recorded muscle activity. Head and trunk displacements, raw and normalized by seated height, and peak head and trunk velocity were compared across age and between maneuvers. Mean EMG was calculated to interpret kinematic findings. Results: Head and trunk displacement and peak velocity were greater in MEB than in AEB in both raw and normalized data ( P ≤ .01). No effect of age was observed ( P ≥ .21). Peak head and trunk velocities were greater in repetition 1 than in repetition 2 ( P ≤ .006) in MEB but not in AEB. Sternocleidomastoid (SCM) mean EMG was greater in MEB compared to AEB, and muscle activity increased in repetition 2 in MEB. Conclusions: Across all ages, head and trunk excursions were greater in MEB than AEB, despite increased muscle activity in MEB. This observation may suggest an ineffective attempt to brace the head or a startle reflex. The increased excursion in MEB compared to AEB may be attributed to differences in the acceleration pulses between the 2 scenarios. These results suggest that AEB systems can use specific deceleration profiles that have potential to reduce occupant motion across diverse age groups compared to sudden maximum emergency braking applied manually.